As he saw it : contributions, memories and reflections of John H. Lounsbury - Caskey, Micki M.; Mertens, Steven B. (Emerald Publishing Limited : Information Age Publishing, Inc., 2021)
"In April 2020, middle level education lost one of its most ardent and influential advocates with the passing of Dr. John H. Lounsbury. His career of over 70 years focused on providing young adolescents with a developmentally appropriate educational program. He is recognized as one of the founders of the modern middle school movement and a founding member of the National Middle School Association, now the Association for Middle Level Education. Through his efforts as an educator, writer, editor, and researcher, John served as a mentor and inspiration to many. John's writings and mentorship continue to influence generations of middle level teachers, colleagues, researchers, and advocates. His legend lives on as we continue his work to improve the lives and educational experiences of young adolescents. This tribute volume is a collection of stories, anecdotes, vignettes, and defining moments that the contributors want to share about Dr. John Lounsbury"-- Provided by publisher.
Keywords: Lounsbury, John H.; Lounsbury, John H. -- Influence.; Middle school education -- United States.; Educators -- United States -- Biography.; elektronické knihy; Biographies.; Biography & Autobiography -- General.; Biography: general.; electronic books